(untitled) (Journal of Social Sciences Review, 2022)
The study aimed to evaluate the textbook of Khyber Pakhtunkhwa at the primary level in comparison to Oxford Modern English Textbook and Cambridge Scholar Standard series Pakistan. The objectives of the study are: (1) to illustrate the importance of textbooks in English language learning at the primary level, (2) to analyze the English textbooks used at the primary level, and (3) to propose/suggest parameters for designing English textbooks for effective English language learning at primary level. The researchers adopted a 75- items evaluative checklist presented by McGrath (2002). This checklist has been selected by the researchers because it fulfils the requirement of the study. The findings show that the English textbook of Khyber Pakhtunkhwa fails to achieve the desired objectives of the English language curriculum. On the basis of the research findings, the researcher concluded that the current English textbook of Khyber Pakhtunkhwa needs to be re-designed in order to address the needs of the primary level students.